2010
DOI: 10.1142/s0219649210002760
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Knowledge Management Practices in Creating Sustainable Competitive Advantage for Business Schools in India

Abstract: Land, labour, capital, raw materials, innovation, human resources, research and development have all been credited as sources of sustainable competitive advantage (SCA). Yet sources of sustainable competitive advantages continuously change, and transformations in the business environment cause shifts in the sources. A viable method to generate sustainable competitive advantages is knowledge management, and this study empirically links the concept of knowledge management to sustainable competitive advantage. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…In the era of knowledge economy, research activities in universities have gained considerable importance (Flagg and others, 2011) and it is impacted by the leadership and cultural factors of KM enablers. It is found that successful KM practices in HEIs can result in the development of sustainable competitive advantage in market (Madan and Khanka, 2010). Likewise, the usage of KM focuses on educational context, whereby faculty members are fully aware of knowledge sharing, but they were mainly focused on teaching activities and sharing of learning resources (Shahzadi and others, 2015;Islam et al, 2013).…”
Section: Challenges Of Knowledge Managementmentioning
confidence: 99%
“…In the era of knowledge economy, research activities in universities have gained considerable importance (Flagg and others, 2011) and it is impacted by the leadership and cultural factors of KM enablers. It is found that successful KM practices in HEIs can result in the development of sustainable competitive advantage in market (Madan and Khanka, 2010). Likewise, the usage of KM focuses on educational context, whereby faculty members are fully aware of knowledge sharing, but they were mainly focused on teaching activities and sharing of learning resources (Shahzadi and others, 2015;Islam et al, 2013).…”
Section: Challenges Of Knowledge Managementmentioning
confidence: 99%
“…The effect of knowledge management on competitive advantage and… | 107 and knowledge are intangible factors associated with this source (Madan & Khanka, 2011). Intangible assets in the form of knowledge management owned by business actors are their unique advantages because it is difficult to imitate other business actors.…”
Section: Introductionmentioning
confidence: 99%
“…Perubahan lingkungan yang cepat menuntut setiap organisasi maupun bisnis segera menanggapi dan beradaptasi. Sebab dalam situasi lingkungan yang semakin kompetitif, salah satu faktor penentu keberhasilan maupun kegagalan organisasi adalah sumber daya manusia yang mendukung operasionalisasinya (Madan et al, 2010).Perubahan lingkungan yang semakin cepat menuntut setiap organisasi untuk segera melakukan revitalisasi anggotanya melalui proses pembelajaran secara berkesinambungan agar memiliki daya tanggap dan daya adaptasi yang cepat terhadap dinamika eksternalnya. Kemajuan teknologi dan ilmu pengetahuan serta 101…”
unclassified